Review: Second harmonic generation spectroscopy as a method for in Situ and online characterization of particle surface properties - Peukert, Wolfgang; Schneider, Lars (Particle & Particle Systems Characterization, 2007)
Non-linear optical spectroscopy is a recently established technique used in the investigation of the properties of colloidal interfaces. Since it is an optical method it is non-invasive, can be applied in situ, and can provide real time resolution. Until recently, only a few papers concerning this method have been published, but these all show the great potential and the large field of applications of the technique. This paper gives an overview of the fundamentals of the technique and its possible applications. © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.
Keywords: Adsorption; Non-linear optical spectroscopy; Online-measurement; Particle surface characterization; Surface charge